Clinical Investigation of Fertility After Uterine Artery Embolization. Issue 2 (February 2022) - Serres-Cousine, Olivier; Kuijper, Fiene Marie; Curis, Emmanuel; Atashroo, Diana
Abstract : (Abstracted from Am J Obstet Gynecol 2021;225:403.e1–403.e22) The most common tumors of the reproductive tract are uterine myomas (leiomyomata, fibroids). These benign tumors are often symptomatic in women of reproductive age and can affect fertility, pregnancy, and childbirth.